HASIL HUTAN BUKAN KAYU MADU SIALANG DI KABUPATEN KAMPAR (Studi Kasus : Kecamatan Kampar Kiri Tengah) - Suhesti, Eni; Hadinoto, Hadinoto (Fakultas Kehutanan Universitas Lancang Kuning, 2015)
Non-Timber Forest Products (NTFPs) is part of a forest ecosystem that has an important role. One of NTFPs which have high economic value and is a source of livelihood of rural communities is often called wild honey or honey sialang. This study aims to: 1) Calculate the potential of the tree and the honey produced sialang 2) Knowing how to manage the honey sialang by society and the problems. Primary data was collected through interviews with respondents using the help of questioners. Data were analyzed descriptively. Potential production of honey from the beehive tree is quite large, each tree can sialang inhabited by about 30 colonies/nest, where the number has further decreased when compared to the time of the woods yet many are converted. In each tree each harvest can be produced approximately 150 kg of honey. Institutional managers honey sialang in the Sub-District of Middle Kampar Kiri is still very minimal. Honey gatherers farmers' organizations have not yet formed, there is only one indigenous group in the village of Penghidupan, whose members are people who are still there family relationship. There are 130 trees sialang and produced 19,500 kg of honey. Honey sialang management is still done traditionally.